Factsheet JUSTNORTH: Conceptualizing Justice for a Sustainable Arctic - JUSTNORTH (Zenodo, 2023)
This document explores the conceptualization of justice in the context of a sustainable Arctic. Drawing on a rich literature on justice, the discussion delves into various frameworks for structuring, examining, and assessing justice and injustice.